Bidirectionality, mediation, and moderation of metaphorical effects: the embodiment of social suspicion and fishy smells - Lee, Spike W S; Schwarz, Norbert (Journal of personality and social psychology, 2012)
Metaphorical effects are commonly assumed to be unidirectional, running from concrete to abstract domains but not vice versa. Noting that metaphorical effects are often found to be bidirectional, we explore how they may be mediated and moderated according to the principles of knowledge accessibility and applicability. Using the example of "something smells fishy" (a metaphorical expression of social suspicion), 7 experiments tested for the behavioral effects of fishy smells on social suspicion among English speakers, the reversed effects of suspicion on smell labeling and detection, and the underlying mechanism. Incidental exposure to fishy smells induced suspicion and undermined cooperation in trust-based economic exchanges in a trust game (Study 1) and a public goods game (Study 2). Socially induced suspicion enhanced the correct labeling of fishy smells, but not other smells (Studies 3a-3c), an effect that could be mediated by the accessibility and moderated by the applicability of metaphorically associated concepts (Studies 4-6). Suspicion also heightened detection sensitivity to low concentrations of fishy smells (Study 7). Bidirectionality, mediation, and moderation of metaphorical effects have important theoretical implications for integrating known wisdom from social cognition with new insights into the embodied and metaphorical nature of human thinking. These findings also highlight the need for exploring the cultural variability and origin of metaphorical knowledge.